2007
DOI: 10.1038/sj.bjc.6603748
|View full text |Cite
|
Sign up to set email alerts
|

Expression of eEF1A2 is associated with clear cell histology in ovarian carcinomas: overexpression of the gene is not dependent on modifications at the EEF1A2 locus

Abstract: The tissue-specific translation elongation factor eEF1A2 is a potential oncogene that is overexpressed in human ovarian cancer. eEF1A2 is highly similar (98%) to the near-ubiquitously expressed eEF1A1 (formerly known as EF1-a) making analysis with commercial antibodies difficult. We wanted to establish the expression pattern of eEF1A2 in ovarian cancer of defined histological subtypes at both the RNA and protein level, and to establish the mechanism for the overexpression of eEF1A2 in tumours. We show that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
0
34
1
2
Order By: Relevance
“…Analysis of the expression profiles using Significance Analysis of Microarrays (SAM) and Linear Models for Microarray Data (LIMMA) revealed 112 significant differentially expressed genes (Figure 3A and Table S7). Some genes such as GPX3 and eEF1A2 have been reported being elevated in ovarian tumors including OCCC [16, 17]. Submission of the gene list for enrichment analysis using Ingenuity Pathway Analysis (IPA) platform demonstrated that most of these genes are involved in cell-to-cell signaling and cell morphology functions (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the expression profiles using Significance Analysis of Microarrays (SAM) and Linear Models for Microarray Data (LIMMA) revealed 112 significant differentially expressed genes (Figure 3A and Table S7). Some genes such as GPX3 and eEF1A2 have been reported being elevated in ovarian tumors including OCCC [16, 17]. Submission of the gene list for enrichment analysis using Ingenuity Pathway Analysis (IPA) platform demonstrated that most of these genes are involved in cell-to-cell signaling and cell morphology functions (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Four novel differentially expressed biomarkers were selected for further studies. eEF1A2 has been implicated as an oncogene in ovarian pathogenesis [16]; PTCH2 is involved in hedgehog signaling and it modulates tumorigenesis in the presence of Ptch1 haploinsufficiency in medulloblastoma and other tumors [22]; PPP1R14B is an inhibitor of protein-phosphatase 1 and is required for cell migration and retraction [23]; XRCC5 is one subunit of the Ku ATP-dependent DNA helicase heterodimer for double-strand break rejoining repair and was found upregulated in ovarian cancer triggered in response to genotoxic stress [24]. Besides overexpression of these four novel biomarkers in OCCC, IHC also showed that they were overexpressed in endometriosis associated with OCCC as compared to endometriosis in patients without cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although eEF1A2 was consistently overexpressed in all four I-144RZ and I-80RZ lines, the q20.13 locus where the EEF1A2 gene is located was amplified only in the I-80RZ lines but not in the I-144RZ lines (8). It has been reported previously that copy numbers of EEF1A2 do not always correlate with expression levels of the gene, indicating that eEF1A2 expression and/or protein levels must also be regulated at other levels (15). The fact that, in our studies, eEF1A2 was overexpressed in lines with and without 20q13 amplification indicates that, similar to Tomlinson’s observations (15, 16), mechanisms besides gene dosage were responsible for its overexpression.…”
Section: Discussionmentioning
confidence: 96%
“…There is increasing evidence that it also exerts oncogenic functions. eEF1A2 is amplified and overexpressed in ovarian cancers (14, 15), and is overexpressed in cancers of the breast and lung (16, 17, 18, 19). It also induces neoplastic properties in NIH3T3 cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…The eEF1A family of peptide elongation factor comprises two isoforms, eEF1A1 and eEF1A2, encoded by different chromosomes but sharing 98% homology (7). Whereas the eEF1A1 is widely expressed in almost all tissues, the eEF1A2 is normally expressed in brain, heart, and skeletal muscle (7)(8)(9). Recent studies have revealed that members of eEF1A family play a critical role in carcinogenesis (10,11).…”
Section: Introductionmentioning
confidence: 99%